1997
DOI: 10.1002/chin.199734217
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Functionalized Fluorescent Dyes and Their Coupling to Amines and Amino Acids.

Abstract: Synthesis of Functionalized Fluorescent Dyes and Their Coupling toAmines and Amino Acids.-A series of novel functionalized benzophenoxazinones (cf. (III), (V), ( VI)), analogues of Nile Red, is synthesized and evaluated for their fluorescence properties. In order to allow labeling of proteins and other biomolecules, the carboxylic acid (VI) is coupled to a range of amino compounds (→ (X), (XII)). -(BRIGGS, M. S. J.; BRUCE, I.; MILLER, J. N.; MOODY, C. J.; SIMMONDS, A. C.; SWANN, E.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…However, we observed that this particular trend for phenol-based fluorophores was not followed by the benzophenoxazine derivative 6b, because in our measurements, its fluorescence intensity showed only a 2-fold decrease compared to the parent 2-hydroxy Nile Red and the expected blue-shift of its maximum emission wavelength was not observed. This result is consistent with an earlier report from Briggs et al showing that the esterification of the hydroxyl group of Nile Red derivatives does not significantly affect their optical properties and prevents the use of such phenol-based fluorophores in the context of fluorogenic probes based on the pro-fluorescence concept (41). Furthermore, during the course of our spectroscopic studies, we observed an anomalous behavior of the pro-fluorophore 6c whose fluorescence significantly increases during incubation with a 8:2 mixture of phosphate buffer (PB, pH 7.4) and acetone.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, we observed that this particular trend for phenol-based fluorophores was not followed by the benzophenoxazine derivative 6b, because in our measurements, its fluorescence intensity showed only a 2-fold decrease compared to the parent 2-hydroxy Nile Red and the expected blue-shift of its maximum emission wavelength was not observed. This result is consistent with an earlier report from Briggs et al showing that the esterification of the hydroxyl group of Nile Red derivatives does not significantly affect their optical properties and prevents the use of such phenol-based fluorophores in the context of fluorogenic probes based on the pro-fluorescence concept (41). Furthermore, during the course of our spectroscopic studies, we observed an anomalous behavior of the pro-fluorophore 6c whose fluorescence significantly increases during incubation with a 8:2 mixture of phosphate buffer (PB, pH 7.4) and acetone.…”
Section: Resultssupporting
confidence: 93%
“…7-Hydroxycoumarin 5a was purchased from Fluka. (Far)-red emitting phenol-based fluorophores 2-hydroxy Nile Red 5b , DDAO 5c , and DAO 5d were synthesized according to previously reported procedures . The fully protected tetrapeptide Ac-Asp(OTMSE)-Glu(OTMSE)-Val-Asp(OTMSE)-OH and its PABA carboxamide derivative 8 were synthesized by using a multistep synthetic procedure recently reported by us .…”
Section: Methodsmentioning
confidence: 99%